Low Oxygen Tension Enhances Osteogenic Potential of Bone Marrow-Derived Mesenchymal Stem Cells with Osteonecrosis-Related Functional Impairment - Lihong Fan; Ruiyu Liu; Jia Li; Zhibin Shi; Xiaoqian Dang; Kunzheng Wang (Hindawi Limited, 2015)
Objective. Glucocorticoids can affect the function of bone marrow-derived mesenchymal stem cells (BMMSCs) adversely and merit the requirement for a strategy to correct this anomaly; we assessed the effect of low oxygen (2%) on BMMSCs from rabbits with osteonecrosis. Methods. Bone marrow-derived mesenchymal stem cells from normal rabbits and rabbits with osteonecrosis were divided into four groups: (1) normal-normoxia group, with normal BMMSCs cultured under 20% oxygen; (2) osteonecrosis-normoxia group, with BMMSCs from rabbits with osteonecrosis cultured under 20% oxygen; (3) osteonecrosis-low oxygen treated group, with BMMSCs from rabbits with osteonecrosis cultured under 2% oxygen; (4) normal-low oxygen treated group, with normal BMMSCs cultured under 2% oxygen. The proliferation, osteogenic, and adipogenic differentiation of MSCs and expression of stemness genes, osteogenic, and adipogenic differentiation markers were investigated. Results. Compared with BMMSCs from normal rabbits, those from osteonecrosis rabbits showed significantly reduced proliferation ability, repressed expression of stemness genes, decreased osteoblasts formation, and increased adipocytes formation, indicating an osteonecrosis-related impairment. Low oxygen (2%) treated BMMSCs from osteonecrosis rabbits showed not only increased proliferation and osteogenic potential but also decreased adipogenic potential. Conclusion. Low oxygen (2%) culture represents a novel strategy to augment BMMSC function affected by glucocorticoids and holds significance for future strategies to treat femoral head osteonecrosis.